Macroeconomic reform in China : laying the foundation for a socialist market economy - Lou, Jiwei; World Bank. (Washington, D.C. : World Bank, 1997)
Macroeconomic Reform in China: Laying the Foundation for a Socialist Market Economy
Includes bibliographical references.